Sosialisasi Perpajakan Memoderasi Pengaruh Kesadaran Wajib Pajak dan Sanksi Perpajakan pada Kepatuhan Wajib Pajak - Hartana, I Made Gilang; Merkusiwati, Ni Ketut Lely Aryani (E-Jurnal Akuntansi, 2018)
The development of an area is heavily dependent on the tax sector. The purpose of this study is to determine the effect of taxpayer awareness and tax sanctions on compliance with motor taxpayers with the socialization of taxation as a moderator. This research was conducted at SAMSAT Tabanan Joint Office. The number of samples used in this study were 100 people obtained by nonprobability sampling method with purposive sampling technique. Data were collected by non-participant observation method and questionnaire. Data analysis technique is done by using multiple linear regression analysis and Moderated Regression Analysis. The results of the research show that taxpayers' awareness and tax sanctions have a positive effect on motor vehicle taxpayer compliance in SAMSAT Tabanan Office. This study also found that the socialization of taxation can strengthen the influence of taxpayer awareness on the compliance of motor vehicle taxpayers in the joint office of SAMSAT Tabanan. K eywords: awareness, sanction, socialization, compliance